The Influence of Regional Budget Management Capability on Organizational Performance With Internal Control Systems as Moderating Variables: Pengaruh Kemampuan Pengelolaan Anggaran terhadap Kinerja Organisasi dengan Sistem Pengendalian Intern sebagai Variabel Moderasi - Violina, Merlin Sintia; Rachmawati, Imelda Dian (Universitas Muhammadiyah Sidoarjo, 2022)
This study aims to see whether the internal control system variabel is able to moderate the ability of budget management on organizational performance. The population used were several employees of the Sidoarjo transportation service office who understood the management of the budget and who carried out or made work plans for the Sidoarjo transportation service whit a total of 50 respondens. The sampling technique used the slovin formula by distributing questionnaires through manuals, namely using paper and distributing them to those concerned so that they got 44 respondens. The data analysis technique used the outer model and inner model and SmartPLS version 3.0 as a tool. Based on the results of this study proves that the ability to manage budget is able to significantly influence organizational performance. In moderation, the internal control system is abel to strengthen the variabel of budget management capability. As a result, it can be concluded that there is quasi-moderation, which means that the variabel that strengthens the correlation of the dependent variabel with the independent variabel and at the same time becomes the independent variable.